2007
DOI: 10.1175/bams-88-4-503
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Verification: A Call for Action and Collaboration

Abstract: A brief verification study of river forecasts suggests the need to link river forecast process improvements more closely to forecast verification results. V erification must be an integral element of forecasting. Well-structured verification provides a means to improve forecast skill, to communicate with nonforecasters regarding resource needs, and to help forecast users optimize their decision making. Within the hydrology community however, few have focused any attention on verifying river forecasts. As a ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 15 publications
3
37
0
Order By: Relevance
“…For example, Welles et al (2007) reported that the hydrologic forecasting skill for some river basins at the US National Weather Service (NWS) River Forecast Centers has hardly improved over the past decade, with above flood-stage hydrologic forecasts beyond three days having very poor skill. This highlights the potential, as well as the need, of assimilating new observations into the operational hydrologic forecasting process to improve the predictive skill and extend the forecast lead time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Welles et al (2007) reported that the hydrologic forecasting skill for some river basins at the US National Weather Service (NWS) River Forecast Centers has hardly improved over the past decade, with above flood-stage hydrologic forecasts beyond three days having very poor skill. This highlights the potential, as well as the need, of assimilating new observations into the operational hydrologic forecasting process to improve the predictive skill and extend the forecast lead time.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there have been renewed calls for the study of hydrologic forecasting science (Welles et al 2007). Welles et al were concerned that decisions surrounding investments to improve forecast accuracy were largely being done based on qualitative impressions from subject matter experts.…”
Section: A a Case For The Science Of Hydrologic Forecastingmentioning
confidence: 99%
“…When floods occur and more information is needed, the local river forecast center (RFC) can decide to publish river-stage forecasts more frequently and for more locations. Welles et al (2007) provides a detailed description of the forecasting process.…”
Section: Datamentioning
confidence: 99%